High school physical education teachers’ perceptions of blended learning one year after the onset of the COVID-19 pandemic - López-Fernández, Iván; Burgueño, Rafael; Gil-Espinosa, Francisco Javier (MDPI, 2021)
The COVID-19 pandemic has altered the educational landscape worldwide. One year after the disease outbreak, blended learning, which combines distance and face-to-face learning, became an alternative to fully online learning to address the demands of ensuring students’ health and education. Physical education teachers faced an additional challenge, given the experiential nature of their subject, but research on teachers’ perspectives is scarce. This study aims to explore high school physical education teachers’ perceptions of the potential, advantages, and disadvantages of the blended learning model of instruction. An online survey was used to register the views of 174 Spanish high school physical education teachers (120 men and 54 women). The main findings revealed that physical education teachers considered that blended learning, compared with full face-to-face learning, implied a work overload, worsened social relationships, and did not help to increase students’ motivation. Likewise, most teachers considered the physical activity performed by students during the blended learning period as being lower than usual. Furthermore, teachers reported that the students from lower-income families were the ones that experienced a lack of technological means the most. These results may guide both present and future policies and procedures for blended physical education. More research is needed to analyze the usefulness of blended learning in high school physical education.
Keywords: Educación física - Estudio y enseñanza - 2021; Enseñanza - Innovaciones; COVID-19; Physical Education; Hybrid education; Online teaching; Secondary school; Adolescents